The irrationality of Petrobras’ divestments in refining - Ribeiro, Cássio Garcia; Silva, Guilherme Jonas Costa da; Almeida, Francielly de Fátima (Brazilian Keynesian Review, 2019)
Petrobras is a Brazilian state-owned company that is one of the largest oil companies in the world. It is internationally recognizedfor being a company at the technological frontier in the segment of exploration and production (E&P) of oil and gas in deepwaters. Also, Petrobras is the publicly traded oil company with the largestproduction of hydrocarbons in the world. This paper aims to investigate the strategies Petrobras currently adopts in refining based on an econometric analysis of panel data. The article is apioneer in the sense of empirically demonstrating that Petrobras consolidated its position in E&P while advancing in the aggregation of value in the refining sector. We can see that income elasticity are less than 1 (about 0.6%). Thisis positive and significant, but the smaller sensitivity than unity demonstrates that the country has broken the barrier to entry into the export sector of oil products.Thus, based on econometric estimates, it is believed that there is a great misunderstanding in the strategy of divestitures and downsizing in the segment of refining.